Important features of home‐based support services for older Australians and their informal carers. (8th February 2015) - McCaffrey, Nikki; Gill, Liz; Kaambwa, Billingsley; Cameron, Ian D.; Patterson, Jan; Crotty, Maria; Ratcliffe, Julie
Abstract In Australia, newly initiated, publicly subsidised 'Home‐Care Packages' designed to assist older people (≥65 years of age) living in their own home must now be offered on a 'consumer‐directed care' (CDC) basis by service providers. However, CDC models have largely developed in the absence of evidence on users' views and preferences. The aim of this study was to determine what features (attributes) of consumer‐directed, home‐based support services are important to older people and their informal carers to inform the design of a discrete choice experiment (DCE). Semi‐structured, face‐to‐face interviews were conducted in December 2012–November 2013 with 17 older people receiving home‐based support services and 10 informal carers from 5 providers located in South Australia and New South Wales. Salient service characteristics important to participants were determined using thematic and constant comparative analysis and formulated into attributes and attribute levels for presentation within a DCE. Initially, eight broad themes were identified: information and knowledge, choice and control, self‐managed continuum, effective co‐ordination, effective communication, responsiveness and flexibility, continuity and planning. Attributes were formulated for the DCE by combining overlapping themes such as effective communication and co‐ordination, and the self‐managed continuum and planning into single attributes. Six salient service features that characterise consumer preferences for the provision of home‐based support service models were identified: choice of provider, choice of support worker, flexibility in care activities provided, contact with the service co‐ordinator, managing the budget and saving unspent funds. Best practice indicates that qualitative research with individuals who represent the population of interest should guide attribute selection for a DCE and this is the first study to employ such methods in aged care service provision. Further development of services could incorporate methods of consumer engagement such as DCEs which facilitate the identification and quantification of users' views and preferences on alternative models of delivery.